Analysis of the determining tariffs for utilization of BLU, A case study in Univercity - Dian Febriani; Wirawan Suhaedi; Yusli Mariadi (International Journal of Applied Finance and Business Studies, 2023)
This study aims to find out what approach is suitable to be used in determining the most ideal amount of asset service rates at Mataram University. The determination of the rates obtained can be a standard in determining service rates for asset leases at the University of Mataram. The type of research used in this study is comperative. The analytical method used in this study is quantitative descriptive. The object of this research is leased service assets, including dormitories, rusunawa, auditorium buildings, dom buildings, cultural arena buildings, football fields, basketball courts, and badminton courts. Data collection techniques used in the form of observation, interviews, and documentation. Based on the results of the study, the most ideal tariff is used for each asset, including dormitories of IDR 1,428,003 (FC), Rusunawa IDR 864,989 (FC), auditorium building IDR 25,293,141 (ABC), dom building IDR 18, 474,205 (ABC), cultural arena building IDR 14,219,504 (ABC), ATM IDR 25,000,000 (Competitors), Football field IDR 435,885 (ABC), basketball court IDR 83,995 (ABC), and badminton court IDR 325,656 (ABC).